Clothes rental services / Muhammad Asyraf Mat Nawi ...[et al.] - Mat Nawi, Muhammad Asyraf; Jelani, Muhammad Arafat; Mohamad Rosli, Muhammad Aiman; Azhar, Danial Aiman (2019)
4AD will be incorporated in year 2019, lead and operate by a group of industry professionals with years of experiences in respective field. Our company focuses in fashion local and international. It is in Second Floor, Southville City, Taman Technology Mint, Bandar Baru Bangi, 43000, Selangor This business proposal presents an overview of business description, activities and goals for 4AD ENTERPRISE within three years forecasted business period. 4AD is a start-up clothes renting retail establishment located at Second Floor, Southville City, Taman Technology Mint, Bandar Baru Bangi, 43000, Selangor. It is surrounded by neighbourhood and university which is a very strategic place to start a business. Its mission is to offer a high-quality clothes and accessories rental at a reasonable and affordable price to meet the demand of the low to higher income metropolitan residents and students. Thus, 4AD will position itself as a place where customers can find the cheapest rental of branded clothes in the easiest way possible which is through application or visit our business premise. The rental includes a broad range of clothes and accessories such as Malay traditional clothes, India traditional clothes, tuxedo, dress, t-shirt and modem clothes. Via our app, the person that uses our app can rent clothes from our company or they can rent out their own clothes as well only if the users pass the requirement needed. 4AD provide variety of its clothes rental at all time during business hour from 10 a.m. until 8 p.m. A few batches of clothes are prepared to ensure clothes needed by the customers can be received on the spot and satisfy our customers. 4AD aims to penetrate the market with 10% of market share among its main competitors (Haurra Sewing Studio and Savanna Boulevaro Shops) with forecast sales of RM 500 in the first month and will increase gradually and it would generate about RM570,500 sales revenue in the first year. The business will experience 10% increment in sales revenue and working capital for the second and third year of business. The total project implementation cost for 4AD is RM 35914. The financial resources will consist of a 15-year small medium enterprise loan equal to RM 9203 and the remaining will acquire from business equity (partner's contribution). In order to ensure that the business will experience sustainable growth, 4AD plans to update its application to make it works more systematic and smoother to satisfy our customer's needs. Our company utilize an application to let the users rent the clothes from us or renting their own clothes. Notwithstanding, it is not limited to clothes only but the accessories, shoes and bags as well as it included in fashion. Nowadays, clothes rental had being issue as the cost way too high. But, our company give the cheapest price in the market which will attract many users to use our service. So, with our innovation, it not only diminishing the expense but rather it additionally accompanies a less difficult technique to facilitate the citizens of our nation to rent clothes. Both sides, us and users will gain the benefits The type of business is a partnership consists of four members who hold important positions in the organization which are General Manager, Administration Manager, Financial Manager, Marketing Manager and Operational Manager. Every one of the accomplices will tirelessly work from 9 .00 a.m. until 7.00 p.m. with the end goal to give the best administrations to our clients. We define our market as a fashion rental. We start the business with hope to achieve outstanding demand from consumer. We even planning to expand our business to the domestic level in the future 4AD did not contend straightforwardly with other organization as we are the just a single to rent the clothes via application in the nation. We trust that we have preferences to stand still in the business and increment the level of our selling will not stopping from year to year.